Combination therapy with rituximab and cyclophosphamide in the treatment of anti-neutrophil cytoplasmic antibodies (ANCA) positive pulmonary hemorrhage: case report - Lehman Thomas JA; Baird Emily M; Worgall Stefan (BMC, 2011)
Abstract Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) with pulmonary hemorrhage is rare in childhood. Standard treatment includes corticosteroids and cyclophosphamide (CYC), which is associated with a high level of toxicity. We report a white female with ANCA positive pulmonary hemorrhage who was treated with cyclophosphamide (CYC) and rituximab (RTX) combination therapy.